NON-FORMAL EDUCATION IN COMMUNITY-BASED WOMEN'S EMPOWERMENT: THE CASE OF THE WOMEN'S SCHOOL ACADEMY IN SAMARINDA - Anita Febriyani; Hepy Tri Winarti; Muhamad Alisalman; Arif Sugianto (SOSIOEDUKASI, 2025)
Women's empowerment is an important aspect of development, because women play a strategic role in improving the welfare of families and communities. In Samarinda City, many women serve as heads of families and face economic and educational challenges. This study aims to analyze the implementation of non-formal education through the Women's School Academy (WSA) program, part of PEKKA (Empowerment of Women Heads of Families), and identify its supporting and inhibiting factors. This study uses a descriptive qualitative approach using in-depth interviews with PEKKA program facilitators and representatives from the Samarinda Women and Children Protection Office (DP2PA), as well as document analysis. The results of the study show that WSA has strengthened the economic independence of participants through providing support for business capacity building, assistance in legal business registration (NIB, PIRT, halal certification), and increasing financial literacy. In addition, the program fosters social solidarity, emotional support, and develops leadership and organizational skills among women. This study concludes that non-formal education through WSA makes a significant contribution to the empowerment of women heads of families and supports sustainable community development in Samarinda.